Implementation of clinical supervision with a collaborative approach to enhance teachers’ pedagogical competence in junior high schools - Alfonrianus Bali; Ade Iriani (Himpunan Pengembang Kurikulum Indonesia, 2024)
Clinical supervision is a systematic approach to mentoring professional teachers. This research aims to improve teachers' pedagogical competence at Bintang Laut Telukdalam Private Middle School through the implementation of clinical supervision with a collaborative approach by the school principal. This type of research is school action research. This research used the Kemmis and Tagart model, which is carried out in 4 stages: planning, implementation or action, observation, and reflection. Data collection techniques used by the researcher are interviews, observation, documentation, and questionnaires. The results of the research show that the implementation of clinical supervision with a collaborative approach by the principal can increase the pedagogical competence of teachers at Bintang Laut Telukdalam Private Middle School, which can be proven by increasing the average teacher pedagogical competency score, namely: before providing clinical supervision the average competency score teacher pedagogy was 63, after providing clinical supervision it increased to 78 in cycle I and 81 in cycle II which was above the specified success criteria, namely 75. From these results, it can be concluded that implementing clinical supervision with a collaborative approach can increase teachers' pedagogy competency at Bintang Laut Telukdalam Private Middle School. Abstrak Supervisi klinis adalah suatu pendekatan yang sistematis dalam pembinaan profesional guru. Penelitian ini bertujuan untuk meningkatkan kompetensi pedagogik guru SMP Swasta Bintang Laut Telukdalam melalui penerapan supervisi klinis dengan pendekatan kolaboratif oleh kepala sekolah. Jenis penelitian ini merupakan penelitian tindakan sekolah. Penelitian ini menggunakan model Kemmis dan Tagart yang merupakan sebuah model penelitian yang dilakukan dengan 4 tahap yaitu perencanaan, pelaksanaan atau tindakan, observasi dan refleksi. Hasil penelitian menunjukkan bahwa pelaksanaan supervisi klinis dengan pendekatan kolaboratif oleh kepala sekolah dapat meningkatkan kompetensi pedagogik guru SMP Swasta Bintang Laut Telukdalam yang dapat dibuktikan dengan peningkatan rata-rata nilai kompetensi pedagogik guru yaitu: sebelum pemeberian tindakan supervisi klinis dengan pendekatan kolaboratif rata-rata nilai kompetensi pedagogik guru 63, setelah pemberian tindakan supervisi klinis dengan pendekatan kolaboratif meningkat menjadi 78 pada siklus I dan 81 pada siklus II yang berada di atas kriteria keberhasilan yang ditentukan yaitu 75. Dari hasil tersebut maka dapat disimpulkan bahwa pelaksanaan supervisi klinis dengan pendekatan kolaboratif dapat meningkatkan kompetensi pedagogik guru SMP Swasta Bintang Laut Telukdalam. Kata Kunci: kompetensi pedagogik guru; pendekatan kolaboratif; supervisi klinis